Case report: Increased efficacy of cetuximab after pembrolizumab failure in cutaneous squamous cell carcinoma - Morecroft, Renee; Phillipps, Jordan; Zhou, Alice; Butt, Omar; Khaddour, Karam; Johanns, Tanner; Ansstas, George (Frontiers in Oncology, 2024)
Immunotherapy is the first-line option for treating advanced cutaneous squamous cell carcinoma (cSCC). However, up to half of patients experience no benefit and treatment resistance, warranting newer therapeutic approaches. Combinatory approaches, including cetuximab, may help overcome immunotherapy resistance and improve response rates in advanced cSCC. We report three cases of metastatic cSCC that achieved significant clinical responses after cetuximab therapy following initial progression on pembrolizumab. We have retrospectively reviewed these cases at a single academic center between 2018 and 2023. All patients initially progressed on pembrolizumab, after which cetuximab (mono-or combination therapy) was added with two complete responses and one partial response. Initial responses were noted within 2 to 7 months of starting cetuximab. While the benefit of cetuximab and immunotherapy in head-and-neck squamous cell carcinoma has growing evidence, information regarding cSCC remains limited. This study adds three cases to the underreported literature on treating advanced cSCC with cetuximab after initially failing immunotherapy.